2021
DOI: 10.1002/jsfa.11072
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes associated with soluble sugar and organic acid accumulation in ‘Huapi’ kumquat (Fortunella crassifolia Swingle) via transcriptome analysis

Abstract: BACKGROUND The levels and ratios of sugar and acid are important contributors to fruit taste. Kumquat is one of the most economically important citrus crops, but information on the soluble sugar and organic acid metabolism in kumquat is limited. Here, two kumquat varieties – ‘Rongan’ (RA) and its mutant ‘Huapi’ (HP) – were used to assess soluble sugar and organic acid accumulation and the related genes. RESULTS Soluble sugars include sucrose, glucose and fructose, while malate, quinic acid and citrate are the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Among them, the content of citric acid accounted for about 70-80% of the total acid. The composition and content of organic acids in citrus fruits have genetic variation [53,54], and the differences are not only manifested between different citrus types [55], also manifested in different varieties of the same species. It has been reported that there are significant differences in the content of citric acid and malic acid in the fruits of the four budding varieties of Guanximi [39].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the content of citric acid accounted for about 70-80% of the total acid. The composition and content of organic acids in citrus fruits have genetic variation [53,54], and the differences are not only manifested between different citrus types [55], also manifested in different varieties of the same species. It has been reported that there are significant differences in the content of citric acid and malic acid in the fruits of the four budding varieties of Guanximi [39].…”
Section: Discussionmentioning
confidence: 99%
“…Contents of non-structural carbohydrates, including sucrose, fructose, and glucose, were quantified by the HPLC system (LC-20AT, Shimadzu, Kyoto, Japan) as previously described [ 70 ]. The total starch content was determined by spectrophotometry (UV-2600, Shimadzu, Kyoto, Japan), and the measurement was performed using a starch reagent kit (G0551F) according to the manufacturer protocol (Suzhou Grace Biotechnology Co., Ltd., Suzhou, China).…”
Section: Methodsmentioning
confidence: 99%
“…During fruit development, upregulating of sucrose synthases enhances sink strength promoting sucrose and starch accumulation and increasing fruit size (Sadka et al, 2019;Feng et al, 2021). SCM also showed downregulation of two ERD6L sugar transporters that might be relevant for sugar accumulation in citrus fruits, especially sugar transporter ERD6-like 7, as reported in kumquats (Wei et al, 2021).…”
Section: Differential Gene Expression In Mandarin Admixtures Versus S...mentioning
confidence: 64%